Efficiently monitoring the ship of financially distressed companies sinking in Iron law of earnings management: Evidence from Pakistan - Muqaddas Khalid; Qaisar Abbas; Mian Sajid Nazir (Cogent Economics & Finance, 2020)
The purpose of this study is to validate the relationship between earnings management and financial distress. Further, it will explore the moderating role of ownership structure for the relationship between earnings management and financial distress which is missing in the current literature. Agency theory and the iron law of earnings management are utilized to develop the framework for this study. Data have been collected from 156 companies listed on the Pakistan Stock Exchange for the period of 2004 to 2017. All the reported results are on a log-odds matric because our dependent variable is binary. The results of the study proved that there exists a positive relationship between earnings management and financial distress and this relationship is negatively moderated by ownership structure. The results of this study are beneficial for investors as well as regulators regarding control mechanisms of ownership structure.
Keywords: 330; agency theory; Earnings management; efficient monitoring; entrenchment behavior; financially distressed companies; financially healthy companies; iron law; logit analysis; moderation; ownership structure